THE GOOD IN POLITICS - Agus Raharjo (Jurnal Dinamika Hukum, 2018)
Hundreds of centuries ago, Aristotle stated in one of his works that the purpose of human life is Entelecheia, the highest kindness in which the goal of every politics. Through that, Aristotle also stated that human is a political creature (zoon politicon), and there are kinds within politics. Politic is one of the ways to reach the good. Time changes, and so does what Aristotle taught, politic now becomes the way on how to get power and the good or kindness is no longer easy to find.